'Remember when lesbian kisses actually meant you were a lesbian?' Historicizing same-sex kissing. Issue 3 (11th November 2011) - BRADY, ANITA
This article considers the methodological possibilities for making political and theoretical sense of a rise in same-sex kissing in the media. A 2010 Gawker article examining the recent abundance of celebrity girl/girl kissing suggested that such kisses are less a positive development in lesbian and gay visibility than a commercially contrived bid for publicity. While acknowledging that the kinds of kisses that the Gawker article highlights cannot unproblematically be described as 'lesbian', this article argues that a media moment in which same-sex kissing has become relatively commonplace represents a significant shift in a cultural landscape dominated by the visual imperatives of heteronormativity. Rather than adjudicating on where such kisses sit on a spectrum of sexual subjectivity, it argues that examining what this might mean for the troubling of heteronormativity might more productively begin by examining the discursive network in which the meaning of 'the same-sex kiss' is produced. In doing so it draws on the framework of genealogical critique deployed by Michel Foucault, Judith Butler and others in the field of queer theory.